(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Computed tomography (CT) is claimed to accurately diagnose many forms of congenital cardiovascular disease in children, particularly in the diagnosis of extracardiac vascular anomalies. The present study is intended to describe the role of CT in the evaluation of congenital cardiovascular disease in children. Methods: The study included children with congenital heart disease (CHD) who underwent CT pulmonary angiography in the Cardiac Imaging Department of Ibrahim Cardiac Hospital & Research Institute, Dhaka between 2015-2017 for investigations of various congenital heart diseases. CT scan was done on Multidetector scanner from Siemens or Philips. Routine preprocedure was done as per protocol of the CT angiography study. Breath holding technique was explained to the older patients who were able to follow breath holding instructions. Plain CT scans of thorax followed by early arterial phases were obtained after negative test dose of the non-ionic contrast by injecting 12 to 40 ml of intravenous contrast media (Iopamidol 350 mg) through antecubital vein by pressure injector at a rate of 1.5 ml/second Scan was obtained 6 seconds after starting of the intravenous contrast. Results: The mean age of the patients was 5.3 ± 0.5 years. Over 60% of the children were male giving a male to female ratio of roughly 3:2. Majority (92%) of children had levocardia with aorta being predominantly originated from the left ventricle (95%). Nearly two-thirds (65%) of the aortas had 50% overriding, 33% had > 50% overriding. Over three-quarters (76%) had left-sided arch and 21% had right-sided arch. Majority (87%) of pulmonary arteries originated from the right ventricle: 50% were of normal size and 44% were narrower than normal. In a few cases both right and left pulmonary artery were absent. In 90% cases right and left pulmonary arteries and veins were confluent. Nearly two-thirds (64%) of the pulmonary arteries were stenosed and 5% did not have any pulmonary valves. Presence of collaterals was commendably high (42%). Seventy percent of the patients had Tetralogy of Fallot (TOF) and over one-quarter (26%) had Patent Ductus Arteriosus (PDA). Interatrial septal defect was found in 21% and intervetricular septal defect in 79% cases. Increased and decreased vascularity of the lungs were found in 13 and 15% of the cases respectively. Other cardiac anomalies were negligible. Conclusion: The findings of the study suggest that the CT pulmonary angiography in the evaluation of CHD has a number of merits and could be done in the diagnosis of pulmonary vascular structures particularly the extra cardiac vascular anomalies. Ibrahim Card Med J 2017; 7 (1&2): 31-36